Differences in Video Media and Flash Card Effectiveness on Knowledge and Attitudes About Body Shaming in Adolescents - Alfiah Rahmawati; Kartika Adyani; Apriliana Eka (EMBRIO: Jurnal Kebidanan, 2021)
Changes in reproductive health can lead to psychological disorders such as body shaming behavior due to changes in the body that occur. Body shaming has been happening lately, such as cases of bullying in both teenagers and cyberspace. The importance of education regarding body shaming as a preventive effort so that the health of each individual is prosperous because physical and mental health are interrelated and based on the results of preliminary studies it can be seen that there are students and students who do not know about body shaming. One of the efforts to prevent body shaming is the provision of education using the media because media is the most influential thing for education today and can influence the development of individual attitudes. This study aims to determine the difference in the effectiveness of the use of video media and flash cards on the knowledge and attitudes of adolescents about body shaming. The research method used is quantitative and uses a Quasi Experiment research design. There are 342 students of SMP Islam Sultan Agung 4 as the population in this study. To get a sample using purposive sampling technique and get 44 respondents for the sample used. From the results of research that has been carried out using Fisher's Test analysis, the significance value of p-value = 1,000 (<0.05). From the results of the research that has been done, it can be concluded that there is no difference between the two media, namely video and flash cards regarding attitudes and knowledge.